2003
DOI: 10.2139/ssrn.438420
|View full text |Cite
|
Sign up to set email alerts
|

Working on the Train? The Role of Technical Progress and Trade in Explaining Wage Differentials in Italian Firms

Abstract: This paper presents firm-level evidence on the dynamics of the relative demand for non-manual workers in Italian manufacturing during the 1990s. The analysis provides a number of interesting results. First, within-firm skill upgrading is the main determinant of the increase in the non-manual wage bill share. By contrast, demand changes associated to trade have shifted employment away from skill-intensive firms. Second, while the relative number of hours worked by skilled workers within firms has risen, the hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…and unskilled labor in the literature (between 1.3 and 1.6) 32 and closer to the elasticity of substitution between P and NP workers estimated by Manasse and Stanca (2003) to be around 0.49-0.67 for Italian manufacturing in the 1990s.…”
Section: B Estimation Resultssupporting
confidence: 80%
“…and unskilled labor in the literature (between 1.3 and 1.6) 32 and closer to the elasticity of substitution between P and NP workers estimated by Manasse and Stanca (2003) to be around 0.49-0.67 for Italian manufacturing in the 1990s.…”
Section: B Estimation Resultssupporting
confidence: 80%
“…Research on technology bias in manufacturing has mostly focused on the bias between labor and capital factors, such as Wang et al [44], Manasse and Stanca [45]. Only a few researchers have examined the relationship between environmental regulatory policies on green TFP and technological progress in the manufacturing sector, as argued by Jaffe et al [46], Yang et al [47] found that environmental regulations are positively correlated with R&D expenditures and that green technology advancement has a positive impact on productivity through a study of the Taiwanese manufacturing industry.…”
Section: Related Research On Manufacturing Sector Sustainability Meas...mentioning
confidence: 99%